2012
DOI: 10.1186/1471-2458-12-968
|View full text |Cite
|
Sign up to set email alerts
|

Burden of paediatric influenza in Western Europe: a systematic review

Abstract: BackgroundInfluenza illness in children causes significant clinical and economic burden. Although some European countries have adopted influenza immunisation policies for healthy children, the debate about paediatric influenza vaccination in most countries of the European Union is ongoing. Our aim was to summarise influenza burden (in terms of health outcomes and economic burden) in children in Western Europe via a systematic literature review.MethodsWe conducted a systematic literature search of PubMed, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 47 publications
8
85
0
7
Order By: Relevance
“…Furthermore, infants and children with underlying disease are at increased risk of severe influenza and influenza-associated mortality [5][6][7]. Several studies have shown that influenza in childhood has considerable socioeconomic impact on the children's households [4,8,9] because children are regarded as the main and most efficient transmitters for spreading influenza in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, infants and children with underlying disease are at increased risk of severe influenza and influenza-associated mortality [5][6][7]. Several studies have shown that influenza in childhood has considerable socioeconomic impact on the children's households [4,8,9] because children are regarded as the main and most efficient transmitters for spreading influenza in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Parents may face additional burdens as influenza spreads throughout their home. A systematic literature review of pediatric influenza in Western Europe found that siblings of children with influenza missed between 1.3 and 6.0 days of school and day care (Antonova et al, 2012). Caretakers may face additional losses of productivity, work, and other emotional or social burdens through these additional illnesses.…”
Section: Further Spreading Of Influenza: Society's Burdenmentioning
confidence: 98%
“…Utilizing the Pediatric Asthma Quality of Life Questionnaire, researchers have shown that influenza lowers quality of life (QoL) in pediatric patients with asthma (Antonova, Rycroft, Ambrose, Heikkinen, & Principi, 2012;Bueving, Van der Wouden, Raat, Bernsen, & De Jongste, 2004). It has also been demonstrated that caregiver QoL is affected by pediatric influenza.…”
Section: Parents' Strain and Quality Of Lifementioning
confidence: 99%
“…Pneumonie mit Vorund Folgeerkrankungen erwartet. Zwar existieren zahlreiche Publikationen, die sich verstärkt nach der Pandemie 2009, ausgelöst durch Influenza-A(H1N1)-pdm2009-Viren, mit Fragen zu Risikofaktoren und möglichen Komplikationen von Influenzaerkrankungen beschäftigt haben [13][14][15][16][17][18], ein Großteil dieser Studien wurde aber im stationären Bereich durchgeführt, sodass vorwiegend schwere Krankheitsverläufe erfasst wurden. Für den ambulanten Bereich hingegen existieren bislang nur wenige longitudinale Studien zu der Fragestellung, ob ein erhöhtes Risiko für Influenza und Pneumonie aufgrund von Vorerkrankungen besteht, sowie zu Komplikationen und langfristigen Folgeerkrankungen, die durch Influenza und Pneumonie geför-dert werden [17,[19][20][21][22][23].…”
Section: Influenza Und Ambulant Erworbene Pneumonie In Hausärztlich Tunclassified